Antihypertensive medications and risk of colorectal cancer in British Columbia - Qi, Jia; Bhatti, Parveen; Spinelli, John J.; Murphy, Rachel A. (Frontiers in Pharmacology, 2023)
There is conflicting evidence for the association between antihypertensive medications and colorectal cancer risk, possibly reflecting methodological limitations of previously conducted studies. Here, we aimed to clarify associations between commonly prescribed antihypertensive medication classes and colorectal cancer risk in a large, retrospective, cohort study. Methods: Using linked administrative data between 1996 and 2017 from British Columbia, we identified a cohort of 1,693,297 men and women who were 50 years of age or older, initially cancer-free and nonusers of antihypertensive medications. Medication use was parameterized as ever use, cumulative duration, and cumulative dose. Cox proportional hazard models were used to estimate hazard ratios (HRs) and associated 95% confidence intervals (95% CIs) for associations of time-varying medication use [angiotensin-converting enzyme inhibitors (ACEIs), angiotensin II receptor blockers (ARBs), beta-blockers (BBs), calcium channel blockers (CCBs), and diuretics] with colorectal cancer risk. Results: There were 28,460 incident cases of colorectal cancer identified over the follow-up period (mean=12.9 years). When medication use was assessed as ever/never, diuretics were associated with increased risk of colorectal cancer (HR 1.08, 95% CI 1.04-1.12). However, no similar association was observed with cumulative duration or cumulative dose of diuretics. No significant associations between the other four classes of medications and colorectal cancer risk were observed.No compelling evidence of associations between antihypertensive medications and colorectal cancer were observed.